2017
DOI: 10.14302/issn.2470-0436.jos-17-1666
|View full text |Cite
|
Sign up to set email alerts
|

Early versus late immunomodulatory therapy in Vogt-Koyanagi-Harada disease

Abstract: Purpose: To evaluate early versus late immunomodulatory therapy (IMT) for patients following initial diagnosis of Vogt-Koyanagi-Harada (VKH) disease. Methods:Retrospective review including all VKH patients seen 5/1/2014 to 4/1/2016 at LAC+USC. Early IMT was defined as starting an immunomodulatory agent within 3 months of corticosteroid initiation.Results: Twenty-seven patients were included, of whom 15 received early IMT and 8 received late IMT.Early IMT patients trended toward greater improvement in vision co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…Case series have demonstrated that multiple regimens may be effective in controlling disease progression and reducing recurrence in patients who are poorly responsive or intolerant of steroids [58][59][60]. However, data are mixed as to whether starting these therapies initially may confer a superior visual outcome or reduced complications as compared to those initially treated with steroids alone and then switched to IMT [61]. Newer biologic agents such as infliximab, adalimumab, rituximab, and interferon alpha for the treatment of VKH have been described in case reports only [62][63][64].…”
Section: Treatmentmentioning
confidence: 99%
“…Case series have demonstrated that multiple regimens may be effective in controlling disease progression and reducing recurrence in patients who are poorly responsive or intolerant of steroids [58][59][60]. However, data are mixed as to whether starting these therapies initially may confer a superior visual outcome or reduced complications as compared to those initially treated with steroids alone and then switched to IMT [61]. Newer biologic agents such as infliximab, adalimumab, rituximab, and interferon alpha for the treatment of VKH have been described in case reports only [62][63][64].…”
Section: Treatmentmentioning
confidence: 99%